Structural Reforms as a Panacea? The European Productivity and Growth Puzzle - Daniel Gros (Intereconomics, 2016)
Most of Southern Europe is only gradually emerging from the devastating effects of the eurozone crisis, with unemployment receding only gradually and a country as big as Italy seemingly stuck in a growth rate below one per cent even as risk premia have fallen dramatically. But Europe is more than a collection of special cases. There is a broader trend, which affects all countries: growth is falling and certainly falling far short of expectations. The recipe almost universally recommended is "structural reforms". But this is a recipe that has been tried intensively in recent decades, and it has failed.
Keywords: 330